2001
DOI: 10.1902/jop.2001.72.6.779
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Between Rheumatoid Arthritis and Periodontitis

Abstract: The results of this study provide further evidence of a significant association between periodontitis and rheumatoid arthritis. This association may be a reflection of a common underlying disregulation of the inflammatory response in these individuals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

43
321
5
37

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 371 publications
(406 citation statements)
references
References 39 publications
43
321
5
37
Order By: Relevance
“…Indeed, RA can increase the incidence and severity of PD (independently or only partially dependent) of oral hygiene status or modifying factors. [4][5][6][7]15,16,35 Accordingly, our results show that PIA increase the severity of ePD in AIRmax mice strain, whereas in AIRmin strain (resistant to PIA development), [25][26][27][28] the severity of ePD was not altered by pristane injection, showing that the development of PIA, and not the pristane injection, is involved in the modulation of ePD severity. Similarly, adjuvant-induced arthritis in rats also results in signs of periodontal destruction.…”
Section: Discussionmentioning
confidence: 65%
See 1 more Smart Citation
“…Indeed, RA can increase the incidence and severity of PD (independently or only partially dependent) of oral hygiene status or modifying factors. [4][5][6][7]15,16,35 Accordingly, our results show that PIA increase the severity of ePD in AIRmax mice strain, whereas in AIRmin strain (resistant to PIA development), [25][26][27][28] the severity of ePD was not altered by pristane injection, showing that the development of PIA, and not the pristane injection, is involved in the modulation of ePD severity. Similarly, adjuvant-induced arthritis in rats also results in signs of periodontal destruction.…”
Section: Discussionmentioning
confidence: 65%
“…[1][2][3] Results from clinical studies point toward a co-morbidity association between chronic periodontitis (PD) and systemic rheumatic diseases, in particular rheumatoid arthritis (RA), described to increase the incidence and/or severity of PD, a chronic infectious inflammatory disease that leads to the destruction of the teeth attachment structures. [4][5][6][7] Chronic PD is the most prevalent chronic inflammatory disease in human beings, in which bacterial species that hosts periodontal biofilm trigger inflammatory and immune responses involved in tissue damage. 8,9 RA is a chronic autoimmune inflammatory disease that possibly arise because of a failure in thymic selection or a peripheral tolerance (the early mechanisms by which immune tolerance is breached and the subsequent event that triggers articular localization is poorly defined), characterized by persistent synovial inflammation and progressive destruction of cartilage and bone in the joints.…”
Section: Introductionmentioning
confidence: 99%
“…There is considerable evidence that the clinical impact of periodontal disease extends beyond the oral cavity (2). Strong associations have been found between periodontitis and a number of systemic conditions, including cardiovascular disease (3,4), preterm delivery and low-birth-weight babies (5), diabetes mellitus (6)(7)(8), and rheumatoid arthritis (9)(10)(11).…”
mentioning
confidence: 99%
“…Participants with RA had significant more missing teeth than participants without RA. Comparing periodontal status in 65 RA patients (according to the ACR criteria 1987) with an age-and gender-matched control group (age range 20e70 years) without RA, Mercado et al [42] found that individuals with RA are more likely to experience more periodontal disease (OR 2.2) compared to individuals without RA. Individuals in the RA group showed significant more missing teeth compared to the non-RA group, an observation that confirms previous findings [43,44].…”
Section: The Bradford Hill Approachmentioning
confidence: 99%